Efficacy of Tranexamic Acid for Hemostasis in Patients Undergoing High Tibial Osteotomy - Suh, Dong Won; Kyung, Bong Soo; Han, Seung-Beom; Cheong, Kuhoang; Lee, Won Hee (The Journal of Knee Surgery, 2018)
Extensive bone bleeding and an uncomfortable hematoma can develop due to the opening gap and space during a medial open high tibial osteotomy (HTO). Tranexamic acid (TXA) has been used in various orthopaedic surgeries to reduce bleeding and wound complications. However, no study has investigated the effect of TXA during HTO. Therefore, the purpose of this study is to evaluate the efficacy of TXA in reducing postoperative blood loss in patients undergoing HTO. The hypothesis is that topical TXA administration will reduce postoperative bleeding in patients undergoing medial opening HTO. Topical TXA (2 g in 20 mL saline) was administered at the osteotomy site in patients (n = 15) who underwent medial open HTO from November 2015 to March 2016. Patients (n = 15) who underwent medial open wedge HTO by the same surgeon from October 2014 to October 2015 were enrolled as a control group for comparison. Drainage volumes on postoperative days (PODs) 1, 2, and 3 as well as hemoglobin (Hb) level on PODs 1, 6, and 13 were measured and compared. Mean total postoperative drainage volume was 246 mL in the TXA group and 377 mL in the control group. Mean drainage volume on POD 1 was 138 mL in the TXA group and 277 mL in the control group (p < 0.05). No differences in drainage volume were detected between the groups on POD 2 or 3. Preoperative Hb levels were 13.0 g/dL in the TXA group and 12.9 g/dL in the control group, which decreased to 11.9 g/dL in the TXA group and 11.2 g/dL in the control group on POD 1. These postoperative Hb differences were significant (p < 0.05). Also, Hb levels were 11.7 and 12.0 g/dL in the TXA group and 11.4 and 11.6 g/dL in the control group on PODs 6 and 13, respectively (p > 0.05). An extensive hematoma requiring additional surgery developed in one case in the control group. No wound complications were detected in the TXA group. Topical TXA was effective for reducing postoperative bleeding after medial open HTO. The level of evidence of the study is Level 3.
Keywords: high tibial osteotomy; hemostasis; tranexamic acid; bleeding